2021
DOI: 10.1051/e3sconf/202132801016
|View full text |Cite
|
Sign up to set email alerts
|

Analysis Of Temperature Effect on Struvite Scales Controlling in A Vertical Reactor

Abstract: Scale is forming and controlling in industrial applications causes the clogs or decreasing in volume flows in the pipes, so increasing maintenance cost can occur as a consequence. Struvite discovered as Magnesium Ammonium Phosphate Hexahydrate (MgNH4PO4.6H2O) and referred as a scale due to the heating process of fluid through pipes. The aim of this research was investigated the temperature effect on process of scales forming and controlling. The process was used a vertical bulkhead reactor. The process starts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…It was shown that the struvite solubility was the lowest and the rate of struvite crystallization was the highest for pH values in the range 8.5–9. [ 10,20–22 ] At a constant pH, the supersaturation increased with the phosphorus concentration and the highest supersaturation values were obtained for a pH equal to 9. [ 23 ] However, as far as the authors are aware, no studies on how high concentrations of phosphorus and ammonium affect the precipitation pH of struvite were reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the struvite solubility was the lowest and the rate of struvite crystallization was the highest for pH values in the range 8.5–9. [ 10,20–22 ] At a constant pH, the supersaturation increased with the phosphorus concentration and the highest supersaturation values were obtained for a pH equal to 9. [ 23 ] However, as far as the authors are aware, no studies on how high concentrations of phosphorus and ammonium affect the precipitation pH of struvite were reported in the literature.…”
Section: Introductionmentioning
confidence: 99%